2017
DOI: 10.7717/peerj.3108
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin extract protects lymphocytes against histone-induced apoptosis

Abstract: Apoptosis of lymphocytes is associated with immunosuppression and poor prognosis in sepsis. Our previous report showed that histones, nuclear proteins released from damaged or dying cells in sepsis, can mediate lymphocyte apoptosis via mitochondria damage. Grape seed proanthocyanidin extract (GSPE), a natural substance with protective properties against oxidative stress, plays a vital role in cell and mitochondria protection. We thus hypothesized that GSPE may play a protective role in histone-induced lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Therefore, we found that OPC can inhibit apoptosis by protecting mitochondria. Similar results have been proven in other kinds of cells (39)(40)(41)(42)(43). In this study, we used chondrocytes derived from mice and did not compare with chondrocytes of other animals.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, we found that OPC can inhibit apoptosis by protecting mitochondria. Similar results have been proven in other kinds of cells (39)(40)(41)(42)(43). In this study, we used chondrocytes derived from mice and did not compare with chondrocytes of other animals.…”
Section: Discussionsupporting
confidence: 74%
“…Intriguingly, our data further reveal that GSP cotreatment rescued the early apoptosis triggered by FB 1 . A study in lymphocytes reported that GSPE could reduce apoptosis induced by extracellular histones by upregulating BCL2 expression [56]. Collectively, our results indicate that the suppressive effects of GSP on apoptosis might be another mechanism against FB 1 toxicity in oocytes.…”
Section: Discussionsupporting
confidence: 54%
“…It has been confirmed that UTI can protect cells from apoptosis though anti-oxidation and reduction of mitochondrial damage. It is known that apoptosis contributes to immunoparalysis and death of sepsis patients (Hotchkiss and Nicholson, 2006; Hotchkiss et al, 2013; Chang et al, 2017b). Anti-apoptosis in sepsis models, via increase in Bcl-2 expression or blocking of CD95, reduced the incidence of sepsis-related mortality (Hotchkiss and Nicholson, 2006; Zhang et al, 2010; Sun et al, 2011; Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%